2021
DOI: 10.1186/s12909-021-02902-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based medicine (EBM) for undergraduate medical students in Sudan: sources of information, knowledge about terms, skills related to EBM and attitude toward EBM in Sudan

Abstract: Background Evidence-based medicine (EBM) is the use of the current best evidence for patient care. Medical students should critically appraise the research evidence to help them during their clinical practice in the future. We conducted this study to assess the skills, terms and attitude toward EBM. Method We conducted a cross-sectional study for medical students from governmental universities. Students completed an online validated questionnaire c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The outcome follows the study findings [ [10] , [11] , [12] , [13] , [14] , [15] ]. Moreover, similar to the findings of [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ], this study believes that information retrieval systems can support students and clinicians to focus on evidence-based dentistry. These research results agree with those of related medical disciplines [ [24] , [25] , [26] , [27] , [28] ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The outcome follows the study findings [ [10] , [11] , [12] , [13] , [14] , [15] ]. Moreover, similar to the findings of [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ], this study believes that information retrieval systems can support students and clinicians to focus on evidence-based dentistry. These research results agree with those of related medical disciplines [ [24] , [25] , [26] , [27] , [28] ].…”
Section: Discussionsupporting
confidence: 87%
“…Clinicians are required to make well-informed judgments on patient care by relying on the most reliable data derived from research studies and clinical guidelines. The ability to effectively obtain, assess, and utilize pertinent medical literature is crucial in order to provide effective healthcare service [ 17 ]. In addition, as dental school draws to a close, the clinical component should include additional instruction and a variety of knowledge retrieval tasks.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the need to add research subjects into the curriculum of medical school is a must [19]. In Sudan, students' positive perceptions towards EBM would raise their awareness of the importance of research, even though their knowledge about methodology, statistics, and scientific literature related to the EBM skills is still low [8], [20].…”
Section: Resultsmentioning
confidence: 99%
“…Students' appreciation of the values or the benefits of statistics on their medical professional career was good enough, but they had a negative to neutral attitudes towards their own intellectual knowledge and skills in statistics [24]. Less understanding of statistics, Mathematics, and the statistical data processing applications in computers, could became the causes of their anxiety which affected negative perceptions towards research [20]. Besides, negative perceptions towards the benefits of research made the students unaware of their professional tasks as medical staff who must do lifelong learning.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in Sudan showed that majority students were using nonscientific learning resources for seeking evidence. 25 A study conducted in Hungary showed that the students who did not take formal training of EBM relied on printed books for seeking evidences, while those who had taken formal training used professional guidelines. 11 The PMC encouraged SDL and seeking evidence-based information from databases in undergradate curriculum a few years ago.…”
Section: Discussionmentioning
confidence: 99%